2008
DOI: 10.1021/ma071805v
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diblock Copolymers toward Controlling the Glass Transition of Thin Polymer Films

Abstract: The physical properties of thin polymer films are often thickness, h, dependent, influenced by confinement and by interfacial interactions between the chains and the external interfaces. We show that the magnitude and film thickness dependence of the average glass transition temperature, T g, of the polystyrene−silicon oxide (PS/SiO x /Si) system are influenced appreciably with the addition of polystyrene-b-poly(methyl methacrylate) (PS-b-PMMA) diblock copolymers. The T g can be “tailored” to increase, or decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
(124 reference statements)
0
10
0
Order By: Relevance
“…In both cases PMMA chains are confined but nevertheless this does not necessarily restrict the chain motions or segmental mobility. Thus T g may either show an increase or a decrease depending on the surface type, the film thickness and the pore size 25–29…”
Section: Resultsmentioning
confidence: 99%
“…In both cases PMMA chains are confined but nevertheless this does not necessarily restrict the chain motions or segmental mobility. Thus T g may either show an increase or a decrease depending on the surface type, the film thickness and the pore size 25–29…”
Section: Resultsmentioning
confidence: 99%
“…With the recent advances in nanotechnology, increasing interest in thin film coatings and nanodevices of polymer materials exacerbates our concerns on the precise understanding of the physical properties and performances of nanodevices related to the segmental dynamics of polymers under confinement. The glass transition temperature ( T g ) is defined as the temperature at which the dynamics of molecules dramatically slow down , and the molecular liquid falls out of equilibrium, manifested as a dramatic increase of the mechanical modulus, an increase in relaxation times, and also in the rise of viscosity by many orders of magnitude. It is a key parameter for characterizing the mobility of polymer chains and determines the temperature range for application of many materials. The glass transition dynamics in thin or ultrathin polymer films (thickness comparable to the radius of gyration of chains) is a fundamental as well as a pressing problem in polymer condensed matter physics. Because of the finite size effects, surface and interface effects, and other impacts, the glass transition dynamics of nanometers-thick polymer films significantly deviates from that in bulk. The glass transition phenomenon in nanostructured systems is a relatively new topic and object of intense scientific debate.…”
Section: Introductionmentioning
confidence: 99%
“…Although considerable approaches have been developed for the T g measurements of thin films, much controversy remains due to apparently contrasting and conflicting results which exhibit variously an increase, ,,, decrease, ,,,, or no change of T g , with the thickness of thin films, as obtained by various techniques. The lack of consensus has provided a strong motivation for development of alternative techniques .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in this study is to understand factors that control the spatial distribution of nanoparticles within thin film mixtures of A- b -B diblock copolymers with homopolymer hosts A, where the copolymers form micelles, with inner cores of the B-block chains and outer coronae of A-block chains. From a technological perspective, micelles may be employed for applications that include nanoparticle encapsulation for drug delivery and antibacterial applications. For these practical situations, it would be important to understand the role of competing enthalpic and entropic interactions on the nanoparticle organization within micellar systems. Recently we demonstrated that gold nanoparticles, onto which P2VP chains are grafted (P2VP-Au), would be sequestered within the P2VP cores of PS- b -P2VP micelles in PS hosts .…”
Section: Introductionmentioning
confidence: 99%